PENGEMBANGAN BAHAN AJAR KITAB TAHAJI UNTUK MENINGKATKAN TAHSINUL KITABAH KELAS 2 MI KEBOKICAK DAPUR KEJAMBON JOMBANG - Nasrul Waton, Muhammad; Humairoh, Zuni; Sholichah, Maulidatus (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2024)
ABSTRAK Mempelajari huruf hijaiyah bagi umat muslim merupakan sebuah keharusan. Sebab, Al-Qur’an sebagai kitab yang wajib dibaca dan dipelajari, ditulis dalam Bahasa arab. Huruf hijaiyah merupakan huruf dalam Bahasa arab yang berarti mengeja, membaca huruf demi huruf. Dalam bahan ajar kitab tahaji yang ada di Madrasah Ibtidaiyah Kebokicak membahas tuntas huruf hijaiyah, di antaranya terdapat adanya indikator pencapaian salah satunya dapat melafalkan dan menuliskan huruf hijaiyah dengan tanda macam-macam harokat. Melalui bahan ajar tersebut, peserta didik dikenalkan juga bentuk huruf-huruf hijaiyah. Namun, masih banyak peserta didik yang belum bisa membedakan dan menuliskan huruf hijaiyah dengan benar. Terdapat rumusan masalah yang diangkat dalam penelitian ini, yakni: (1) Bagaimana proses pengembangan bahan ajar kitab Tahaji dalam meningkatkan Tahsinul Kitabah? (2) Bagaimana efektifitas pembelajaran sebelum dan sesudah adanya bahan ajar Tahaji dalam meningkatkan Tahsinul Kitabah kelas 2 Madrasah Ibtidaiyah Kebokicak? (3) Bagaimana penerapan pengembangan bahan ajar kitab Tahaji dalam meningkatkan Tahsinul Kitabah kelas 2 Madrasah Ibtidaiyah Kebokicak?Penelitian ini menggunakan metode Research and Development (R&D) dengan model pendekatan Borg and Gall. Instrument pengumpulan data yang digunakan yaitu wawancara, observasi, dan angket.subjek dalam penelitian ini adalah peserta didik kelas 2 MI Kebokicak Dapurkejambon Jombang.Hasil penelitian ini menunjukkan bahwa (1) penerapan bahan ajar kitab tahaji diterapkan melalui pengembangan Borg and Gall dengan melalui beberapa prosedur pengembangan. (2) peserta didik sangat antusias dan lebih mudah memahami pelajaran tahaji karena terdapat contoh cara penulisan huruf hijaiyah dan banyaknya latihan soal serta berbagai gambar yang menarik. (3) bentuk peningkatan tahsinul kitabah dapat dilihat dari hasil instrument penilaian dengan rata-rata nilai 69% sebelum menggunakan bahan ajar kitab tahaji dan 87% setelah menggunakan bahan ajar kitab tahaji untuk meningkatkan tahsinul kitabah. Kata Kunci: Pengembangan, Tahaji, Tahsinul Kitabah ABSTRCT Learning the hijaiyah letters for Muslims is a must. Because, the Koran, as a book that must be read and studied, is written in Arabic. Hijaiyah letters are letters in Arabic which mean spelling, counting letters, reading letter by letter. In the teaching materials on the book of Tahaji at Madrasah Ibtidaiyah Kebokicak, the hijaiyah letters are thoroughly discussed, including indicators of achievement, one of which is being able to pronounce and write the hijaiyah letters with the punctuation marks fathah, kasroh, dlommah, fathatain, kasrotain, dlommatain, mad, layyin, sukun and tasydid. Through these teaching materials, students are also introduced to the shape of the hijaiyah letters. However, there are still many students who cannot distinguish and write hijaiyah letters correctly. Therefore, the researcher adopted the Tahaji Book teaching material with Tahsinul Kitabah as teaching material from the results of the development of the Tahaji Book in class 2 Harokat material. There is a problem formulation raised in this research, namely: (1) What is the process of developing teaching materials for the Tahaji book in improving the Tahsinul Kitabah? (2) What is the effectiveness of learning before and after Tahaji teaching materials in improving Tahsinul Kitabah grade 2 Madrasah Ibtidaiyah Kebokicak? (3) How is the development of Tahaji book teaching materials implemented in improving Tahsinul Kitabah class 2 at Madrasah Ibtidaiyah Kebokicak? This research uses the Research and Development (R&D) method with the Borg and Gall approach model. The data collection instruments used were interviews, observations and questionnaires. The subjects in this research were grade 2 students at MI Kebokicak Dapur Kejambon Jombang. The results of this research show that (1) the application of the Tahaji book teaching materials is used using lecture and practice methods. (2) the application of the Tahaji book teaching materials is implemented through the development of Borg and Gall through several development procedures. (3) students are very enthusiastic and understand the tahaji lesson more easily because there are examples of how to write hijaiyah letters and lots of practice questions as well as various interesting pictures. (4) the form of improvement in tahsinul kitabah can be seen from the results of the assessment instrument with an average score of 69% before using the teaching material of the book of tahaji, while 87% after using the teaching material of the book of tahaji to improve tahsinul kitabah. Keywords: Development, Tahaji, Tahsinul Kitabah